Unit commitment problem in deregulated environment - Bisanovic, Smajo; Hajro, Mensur; Dlakic, Muris (International journal of electrical power & energy systems, 2012)
► Paper presents MILP model for unit commitment problem on day-ahead market. ► Model requires a single type of binary variables used in modelling on/off decision. ► Bilateral contracts are included in this model to reduce risk of profit deviation. This paper addresses the self-scheduling problem of generation companies owning thermal power units considering bilateral contracts and day-ahead market. This approach allows precise modelling of variable costs, start-up costs and comprehensive system of constraints. The self-scheduling model is formulated as deterministic optimization problem in which expected profit is maximized by 0/1 mixed-integer linear programming technique. Solution is achieved using the homogeneous and self-dual interior point method for linear programming, with a branch and bound optimizer for integer programming. The effectiveness of the proposed model for optimizing the thermal generation schedule is demonstrated through the case study with detailed discussion.